César González Ochoa, La polis. Ensayo sobre la ciudad en Grecia antigua, Universidad Nacional Autónoma de México, México, 2004, 133 pp. ISBN: 970-32-2042-8 (Minerva, 2019)
Review: César González Ochoa, La polis. Ensayo sobre la ciudad en Grecia antigua, Universidad Nacional Autónoma de México, México, 2004, 133 pp. ISBN: 970-32-2042-8